O Papel do gerente nos programas de relacionamento: um estudo de caso múltiplo em três instituições bancárias - Pinheiro Neto, Miguel (2015)
This search of the perceived importance of the relationship in the marketing strategies of action for companies in general and the banking sector in particular. Presents a discussion of the conflicts between the customer relationship programs proposed by commercial banks in Fortaleza and the level of adherence of these programs by the relationship managers. Has as main objective to analyze the relationship manager's role is adherent to the relationship program with clients developed by banks in Fortaleza. Through a qualitative and quantitative research will seek to identify and explain this adherence, or not, of the managers to relationship programs offered by banks. The results confirm the assumptions raised by research that there are conflicts between the role of the relationship manager and the determinations of the banks' relationship programs under review.